Didactive And Review Of Axiology Theorem Of Da'wah Science Development Of Islamic Society In Supporting Social Workers - Mubasit (International Journal of Educational Research & Social Sciences, 2021)
The da'wah communication strategy is the basic policy of da'wah organizations which are options and alternatives that are directly related tothe achievement of da'wah goals, namely guiding relationships, organizing communication, developing and improving mad'u action patterns so that they are in accordance with Islamic teachings after considering internal conditions and external conditions. , then the main problem is: "the communication strategy of da'wah in empowering the labor community in Panjang District, Bandar Lampung City to improve the practice of religious implementation". The importance of da'wah communication to the poor is an effort to help them maintain unity by enabling them to influence and react to one another. Where the role of da'wah communication in social relations is clearly the main foundation for realizing social interaction which in Islamic teachings is known as silaturrahim. To find out the inhibiting factors in preaching to the labor community.This research is a field research, which is a research conducted in real life. The nature of this research is descriptive. The main method in this study the author uses the interview method, namely the method of data collection by way of question and answer between one or more parties to obtain the necessary information. The observation method is a way of collecting data by systematically recording the symptoms that appear on the object of research when the research takes place. The documentation method is a collection of verbal data in the form of writing, called narrow meaning documentation. Meanwhile, the data analysis uses analytical and qualitative methods, meaning that the analysis is based on quality (value or price) and not based on numbers or quantities. The da'i communication strategy for the da'i in Panjanga District is to provide motivation, including through da'wah messages (materials) that are conveyed to the community. With the guidance carried out by the da'I in Panjang District covering religious matters such as praying 5 times a day, memorizing prayers, managing corpses and protecting the environment. The biggest inhibiting factor felt was the factor of mad'u, especially in terms of understanding the message (sematic), closed to change (self-image), and motivation where this was marked by the passiveness of the communicant in receiving da'wah from the da'i, in the sense of da'i cannot fully know the semantic knowledge possessed by the community.